Why do emitters trade carbon permits? Firm-level evidence from the European emission trading scheme - Aleksandar Zaklan (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
The creation of the EU's Emission Trading Scheme (EU ETS) has turned the right to emit CO2 into a positively priced intermediate good for the affected firms. Firms thus face the decision whether to source compliance with the EU ETS within their boundaries or to acquire it through the permit trade. However, a combination of internal abatement, free permit allocation and exibility to shift the use of their allocation across time creates opportunities to achieve compliance with the EU ETS without entering the permit trade. This paper aims to identify firm-level determinants of participation in and the extent of the permit trade while recognizing the possibility of zero trade flows leading to selection bias if unaccounted-for. We construct a firm-level dataset incorporating transaction-level information from both EU ETS operator and person holding accounts, thus representing the entire system-wide permit trade by CO2 emitters. We cover the supply and demand sides of the permit trade, both inter- firm and intra-firm, and account for a wide set of firm-level characteristics using firms' balance sheet information. A detailed descriptive analysis documents salient features of the firm-level permit trade. We then jointly model firms' participation and amount decisions while allowing for possible self-selection into trading. Our results suggest that participation in the permit trade is driven by a combination of firm-specific factors existing independently of the EU ETS, such as size, sector and ownership structure, and market-specific characteristics resulting from the firms' inclusion in the EU ETS, such as the value of the firms' free permit endowment and their relative allowance position. We find that amounts traded are mostly driven by market-specific factors. In contrast to the literature on the firm-level determinants of the general goods trade we do not find self-selection into trading.
Keywords: F14; F18; Q54; C34; 330; EU ETS; carbon emission permits; firm-level trade; inter-firm trade; intra-firm trade